Analysis of the Principal's Role in Improving the Quality of Primary School Management - Kadariah, Kadariah (Program Pascasarjana Universitas Negeri Makassar, 2019)
This study aims to: (1) describe the principal’s strategies to plan, organize, actuate, and control the school programs to improve the quality of education at SMP 1 Cilawu; and (2) describe constraints in the improvement of the quality of education. This was a case study with qualitative approach. The research subjects included teachers and educational personnel. The results of the study used the principal’s as a manager: (1) plans programs by specifying the needs for teachers and educational personnel who will carry out duties, programs in the form of policies and the curriculum that will be implemented, and policies to add the time slot for the guidance and counseling subject by two hours a week; (2) makes an organizational structure by involving students’parents through the school committee and completing infrastructure facilities that the school needs; (3) gives examples of how to work well and calmly, motivation, and rewards to the personnel morally and materially, improves welfare, sends teachers and educational personnel to trainings, and motivates senior teachers to have spirit of lifelong education; and (4) controls the output, teaching and learning processes, and students from the enrolment to the graduation. (5) The constraints include the facts that there are personnel who are not disciplined, there is a lack of communication between the principal and some of the personnel, and the school operation aid funds do not match the school’s needs..